2001
DOI: 10.3168/jds.s0022-0302(01)74726-1
|View full text |Cite
|
Sign up to set email alerts
|

Rumen Acid Production from Dairy Feeds. 1. Effects on Feed Intake and Milk Production of Dairy Cows Offered Grass or Corn Silages

Abstract: Earlier studies developed a new approach to feed evaluation, measuring the net acid load that develops during rumen fermentation. Two concentrates were formulated to be isoenergetic and isonitrogenous, with extremes of rumen acid load. A third treatment comprised a 50:50 mixture of these concentrates. These concentrates were evaluated along with ryegrass silage and corn silage. The feeds were evaluated in a continuous culture system adapted to deliver and record the quantities of acid or alkali needed to maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The data were not consistent with the findings of Martin et al [24] who observed no difference in ruminal pH value of steers given either flint or dent corn. In diets containing large amounts of maize silage, animal performance may be adversely affected by subacute rumen acidosis [10]. The possibility of manipulating rumen pH value by choosing an adequate genotype, is therefore of great practical importance.…”
Section: Digestion Of Maize Starch and The Effect Of Grain Type On Rumentioning
confidence: 99%
“…The data were not consistent with the findings of Martin et al [24] who observed no difference in ruminal pH value of steers given either flint or dent corn. In diets containing large amounts of maize silage, animal performance may be adversely affected by subacute rumen acidosis [10]. The possibility of manipulating rumen pH value by choosing an adequate genotype, is therefore of great practical importance.…”
Section: Digestion Of Maize Starch and The Effect Of Grain Type On Rumentioning
confidence: 99%
“…A negative correlation between dietary PAPV and milk protein was noticed, although the relation was not significant in the present study. Dewhurst et al (2001) reported that milk protein concentration was not influenced by concentrate type when using corn silage as a roughage source but tended to be higher when high acid load concentrates were fed with grass silage. However, the relationship was not sound, which indicates that milk protein did not fluctuate to a great extent based on diet.…”
Section: Resultsmentioning
confidence: 98%
“…This is somewhat different from previous results. For instance, increasing concentrate acidogenicity was negatively related to dry matter intake (Wadhwa et al, 2001b) and milk yield (Dewhurst et al, 2001), with variable effects on milk composition. The PAPV of TMR used in the experimental farms ranged from 5 to 15; therefore, the PAPV was not high enough to yield a negative impact on production traits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, rumen pH is one of the most critical determinants for rumen function as cellulolytic bacteria fail to grow below pH 6.0. While, early studies have reported that low rumen pH has negative effects on appetite (Shinozaki, 1959), microbial yield (Oliveira et al, 1997;Russell and Dombrowski, 1980), methane production (Lee et al, 2003), dry matter intake (Dewhurst et al, 2001), milk yield (Wanapat et al, 2009) and fiber digestion (Smith et al, 1973;Stewart, 1977;Terry et al, 1969).…”
Section: Resultsmentioning
confidence: 99%